Case report: Identification of a novel variant p.Gly215Arg in the CHN1 gene causing Moebius syndrome - Manso-Bazús, Carmen; Spataro, Nino; Gabau, Elisabeth; Beltrán-Salazar, Viviana P.; Trujillo-Quintero, Juan Pablo; Capdevila, Nuria; Brunet-Vega, Anna; Baena, Neus; Jeyaprakash, A Arockia; Martinez-Glez, Victor; Ruiz, Anna (Frontiers in Genetics, 2024)
Moebius Syndrome (MBS) is a rare congenital neurological disorder characterized by paralysis of facial nerves, impairment of ocular abduction and other variable abnormalities. MBS has been attributed to both environmental and genetic factors as potential causes. Until now only two genes, PLXND1 and REV3L have been identified to cause MBS.We present a 9 years-old male clinically diagnosed with MBS, presenting facial palsy, altered ocular mobility, microglossia, dental anomalies and congenital torticollis.Radiologically, he lacks both abducens nerves and shows altered symmetry of both facial and vestibulocochlear nerves. Whole-exome sequence identified a de novo missense variant c.643G>A; p.Gly215Arg in CHN1, encoding the α2-chimaerin protein. The p.Gly215Arg variant is located in the C1 domain of CHN1 where other pathogenic gain of function variants have been reported. Bioinformatic analysis and molecular structural modelling predict a deleterious effect of the missense variant on the protein function.Our findings support that pathogenic variants in the CHN1 gene may be responsible for different cranial congenital dysinnervation syndromes, including Moebius and Duane retraction syndromes. We propose to include CHN1 in the genetic diagnoses of MBS.